Professional rugby on the Celtic fringe - Vincent Hogan; Patrick Massey (University College Dublin, UCD Centre for Economic Research, 2020)
The design of sports leagues has significant financial implications for the organisers and member teams and for the relative success or failure of the individual clubs. Using the Pro 14 rugby league as an example we show how the structure of the league has influenced the success of the league overall and that of individual teams. We use variation in rules across time and space to identify their effects. We show how match attendance has been boosted by measures such as reducing the number of Sunday matches and the introduction of play-offs. We also show that the Pro14 have increased broadcast revenue largely through geographic expansion into larger broadcast markets. Furthermore, this has occurred without an adverse effect on match attendance.
Keywords: Z23; D24; 330; Sports Finance; Productivity